Pancreatic cancer surgery: the new R-status counts - Strobel, Oliver; Hank, Thomas; Hinz, Ulf; Bergmann, Frank; Schneider, Lutz; Springfeld, Christoph; Jäger, Dirk; Schirmacher, Peter; Hackert, Thilo; Büchler, Markus W. (Annals of surgery, 2017)
Objective: To assess the relevance of resection margin status for survival outcome after resection and adjuvant therapy for pancreatic cancer. Background: The definitions for R0 and R1 margin status after resection for pancreatic cancer are controversial. The strict definition of R0 requiring a 1 mm tumor-free margin is not commonly accepted. Reported R0/R1 rates and associated survival are highly heterogeneous. Methods: A standardized protocol with rigorous assessment of circumferential margins and the R0 definition with a 1 mm free margin were introduced into clinical routine in 2005. From a prospective database, patients undergoing pancreatoduodenectomy for pancreatic adenocarcinoma between January 1, 2006 and December 12, 2012 were identified. The rates of R0 (≥1 mm margin), R1 (<1 mm clearance), and R1 (direct margin involvement) status and associated survival were assessed by uni- and multivariable analyses. Results: Of 561 patients included, 112 patients (20.0%) had R0 and 449 patients (80.0%) had R1 resections, including 123 (21.9%) R1 (≤1 mm) and 326 (58.1%) R1 (direct) resections. A total of 438 (85.9%) received adjuvant therapy. With R0, R1 (<1 mm), and R1 (direct) status the median survival times and 5-year survival rates were 41.6, 27.5, and 23.4 months; and 37.7%, 30.1%, and 20.3%, respectively (P < 0.0001). By multivariable analysis, margin status was confirmed to be independently associated with survival. Conclusions: In the context of adjuvant therapy, the resection margin status remains an important independent determinant of postresection survival. R0/R1 resection rates and associated survival vary significantly with the definitions used. An international consensus is urgently needed to achieve comparability with respect to studies and protocols on patients with adjuvant therapy.
Gesehen am 22.05.2018